2011
DOI: 10.1016/j.jfranklin.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fuzzy model using genetic algorithm for process control application

Abstract: A technique for the modeling of nonlinear control processes using fuzzy modeling approach based on the Takagi-Sugeno fuzzy model with a combination of genetic algorithm and recursive least square is proposed. This paper discusses the identification of the parameters at the antecedent and consequent parts of the fuzzy model. For the antecedent fuzzy parameters, genetic algorithm is used to tune them while at the consequent part, recursive least squares approach is used to identify the system parameters. This ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Then, the MOHGA and the recursive least squares estimator (RLSE) are used to obtain the optimized fuzzy models. A fuzzy modeling approach for the identification of nonlinear control processes was discussed in Yusof et al (2011). This approach is based on a combination of genetic algorithm and recursive least squares.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the MOHGA and the recursive least squares estimator (RLSE) are used to obtain the optimized fuzzy models. A fuzzy modeling approach for the identification of nonlinear control processes was discussed in Yusof et al (2011). This approach is based on a combination of genetic algorithm and recursive least squares.…”
Section: Related Workmentioning
confidence: 99%
“…Fuzzy logic control has become increasingly popular in recent years [26]. Its ability to control imprecise or vague processes has been used to perform the control of numerous industrial applications [27].…”
Section: Software Implementationmentioning
confidence: 99%
“…[14][15][16] Also, in modeling researches, it is used to optimize the ANN and FL model parameters. [17][18][19] Despite the significant role of FT on PVC properties, the studies reported in declaring or characterizing effects of material and processing variables are few. Specially, no modeling research is reported except the article published by the authors.…”
Section: Introductionmentioning
confidence: 99%